Experimental Investigations of Deformation Pathways in Nanowires - Sedlmayr, Andreas (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2012)
This work deals with the experimental investigation of the mechanical properties of nanowires. Experiments are conducted in a dedicated system inside the electron microscope. The mechanical response of various material systems is probed, the underlying deformation mechanisms are elucidated and subsequently put into context with mechanical size effects.